Expert consensus for managing pregnant women and neonates born to mothers with suspected or confirmed novel coronavirus (COVID‐19) infection. Issue 2 (1st April 2020) - Chen, Dunjin; Yang, Huixia; Cao, Yun; Cheng, Weiwei; Duan, Tao; Fan, Cuifang; Fan, Shangrong; Feng, Ling; Gao, Yuanmei; He, Fang; He, Jing; Hu, Yali; et al.
Abstract: Objective: To provide clinical management guidelines for novel coronavirus (COVID‐19) in pregnancy. Methods: On February 5, 2020, a multidisciplinary teleconference comprising Chinese physicians and researchers was held and medical management strategies of COVID‐19 infection in pregnancy were discussed. Results: Ten key recommendations were provided for the management of COVID‐19 infections in pregnancy. Conclusion: Currently, there is no clear evidence regarding optimal delivery timing, the safety of vaginal delivery, or whether cesarean delivery prevents vertical transmission at the time of delivery; therefore, route of delivery and delivery timing should be individualized based on obstetrical indications and maternal–fetal status. Abstract : Currently, there is no clear evidence regarding optimal delivery timing or route of delivery for pregnant women with COVID‐19 infection; these should be individualized based on obstetrical indications and maternal–fetal status.